Qualities of food - Harvey, Mark (Manchester University Press, 2004)
This book addresses current controversial debates about food quality. What is it that makes people decide that food is of good, or alternatively of dubious, 'quality'? How food is produced, how it is prepared, how it tastes and in what circumstances it is consumed are all dimensions of its quality. Chapters address a number of intriguing questions: how do people make judgements about taste?; how do such judgements come to be shared by groups or people?; what social and organisational processes result in foods being certified as of decent or proper quality?; how has dissatisfaction with the food system been expressed?; what alternatives are thought to be possible? The book shows that there are many different answers to such questions because there are many different attributes of food about which judgements may be made. The complexity and the significance of the evaluations of the foods we eat are analysed from a variety of perspectives, by sociologists, economists, geographers and anthropologists. The first part of the book focuses on theoretical and conceptual issues, the second part considers processes of formal and informal regulation, while the third part examines social and political responses to industrialised food production and mass consumption. Qualities of food will be of interest to researchers and students in all the social science disciplines that are concerned with food, whether marketing, sociology, cultural studies, anthropology, human nutrition or economics.